Behavioral Determinants of Compliance with Iron Tablet Consumption in Pregnant Women: An Analytical Study in Primary Obstetric Services - Maya Sari (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Adherence to iron tablet consumption among pregnant women remains suboptimal despite its critical role in preventing iron deficiency anemia. Previous studies have identified various influencing factors; however, evidence regarding the relative contribution of behavioral determinants, particularly the role of the husband’s support in primary obstetric care, remains limited. This study aimed to analyze the influence of knowledge, attitudes, and husbands’ support on adherence to iron tablet consumption among pregnant women. An analytical cross-sectional study was conducted involving 47 pregnant women in primary obstetric services. Data were collected using a validated questionnaire and analyzed using Fisher’s Exact test and binary logistic regression to identify the most dominant factor. The results showed that 63.8% of respondents were non-adherent to iron tablet consumption. Bivariate analysis indicated significant associations between husband’s support (p=0.001), knowledge (p=0.024), and attitude (p=0.018) with adherence. Multivariate analysis revealed that husband’s support was the strongest predictor of adherence (OR=9.15; 95% CI: 2.45–34.1), followed by attitude (OR=5.22) and knowledge (OR=4.14). In conclusion, the husband’s support plays a pivotal role in improving adherence to iron tablet consumption among pregnant women. Therefore, interventions in primary obstetric care should incorporate partner involvement in antenatal education to strengthen reinforcing factors and improve maternal health outcomes Keywords: Husband's Support, Compliance, Knowledge, Attitude, Iron Tablets